Value of International Legal Acts in Relation to the Criminal Legislation of the Republic of Kazakhstan - KONYSBAI, Bakytkul Menlenkyzy; KUANALIYEVA, Guldana Amangeldiyevna; TURSYNKULOVA, Dinara Akhanovna (Journal of Advanced Research in Law and Economics, 2016)
The article with the provisions of the criminal law of the Republic of Kazakhstan studied various kinds of international legal instruments and their legal norms and the use in the course of the preliminary investigation and the judicial proceedings. Identified gaps of criminal procedure regulations and the ways of implementation of the norms of international legal acts, including treaties of Kazakhstan, subject to the provisions of the criminal procedure law and other legal acts. The author's position on the Application of Standards intercity rights in the criminal procedure of the Republic of Kazakhstan. Proposals for improving the criminal procedural legislation of the Republic of Kazakhstan in connection with the implementation of international legal norms. The theoretical value of this work is to justify the need to include in the system of sources of criminal procedural law of the Republic of Kazakhstan recognized principles and norms of international law, the international treaties of the Republic of Kazakhstan, as well as in determining the forms of implementation of international legal norms. In the article for the first time subjected to scientific analysis of some questions to fully understand the content, significance and use in criminal proceedings of various legal force and legal value of international acts. The paper thoroughly discussed the issues of interaction of international and criminal procedural law, learn the basic set of problems arising in the implementation of this interaction. The studies contribute to defining areas for further theoretical development and improvement of practical activities to do on the basis of research findings can be used to further develop the regulatory framework for international cooperation of investigation bodies and courts of the Republic of Kazakhstan.